Differential expression of maturation and activation markers on NK cells in patients with active and latent tuberculosis. Issue 5 (10th December 2021) - Albayrak, Nurhan; Dirix, Violette; Aerts, Laetitia; Van Praet, Anne; Godefroid, Audrey; Dauby, Nicolas; Windey, Patricia; Muylle, Inge; Mascart, Françoise; Corbière, Véronique
Abstract: NK cells were recently suggested to be important for the initial control of M. tuberculosis infection. The phenotypes of the 3 main NK blood subsets, CD56 bright, CD56 dim, and CD56 neg cells, were characterized by flow cytometry in a cohort of 81 prospectively enrolled subjects (21 untreated patients with active tuberculosis -aTB-, 35 latently TB infected -LTBI- subjects, and 25 non-infected controls), using 9 different mAbs added to whole blood. Compared to LTBI subjects, patients with aTB had lower proportions of total NK cells, lower proportions and numbers of CD56 neg cells expressing early maturation markers (CD161, NKp30, NKp46), but higher density of NKp30 and NKp46 expression on both CD56 neg and CD56 dim subsets, associated with higher expression of granzymes A/B. They also had higher proportions of activated CD69 pos cells within all 3 NK cell subsets and, the percentage of CD69 pos CD56 dim cells among CD69 pos and/or NKG2C pos NK cells was identified as a potential biomarker to discriminate aTB from LTBI. LTBI subjects were in contrast characterized by higher expression of late maturation markers (CD57, KIR molecules) on the CD56 neg subset, by higher proportions of NKG2C pos KIR pos CD56 dim NK cells, and by higher in vitro IFN-γ production than patients with aTB. Thus, the in-depth phenotypic characterization of blood NK cell subsets provides new insights on possible functional modifications and the potential role of NK cells in the control of M. tuberculosis infection in humans. Graphical Abstract: Whereas the numbers of the main NK cells subsets are normal in M. tuberculosis-infected patients, detailed phenotypic characterization revealed several differences related to functional modifications.